2001
DOI: 10.1017/s1360641701002738
|View full text |Cite
|
Sign up to set email alerts
|

The Social Competence of Children with Attention Deficit Hyperactivity Disorder: A Review of the Literature

Abstract: This article reviews research conducted over the past 20 years on the social competence of children with Attention Deficit Hyperactivity Disorder (ADHD). A substantial body of research suggests that children with ADHD experience significant interpersonal difficulties. The social competence of ADHD children is considered using three indices : typical social behaviours or social functioning, internal cognitive structures relating to the behaviours, and the products or outcomes of their social functioning. Possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
59
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 31 publications
1
59
0
3
Order By: Relevance
“…Numerous studies have confirmed the behavior problems and social competence impairments of children with ADHD, stressing their high levels of aggression, defiant, disruptive and intrusive behavior, poor peer interactions and impaired interpretation of social situations (Henker & Whalen, 1989;Henker & Whalen, 1999;Nixon, 2001;Stormont, 2001).…”
Section: Adhd and Social Skillsmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies have confirmed the behavior problems and social competence impairments of children with ADHD, stressing their high levels of aggression, defiant, disruptive and intrusive behavior, poor peer interactions and impaired interpretation of social situations (Henker & Whalen, 1989;Henker & Whalen, 1999;Nixon, 2001;Stormont, 2001).…”
Section: Adhd and Social Skillsmentioning
confidence: 99%
“…The main indicator of social competence within this body of research is the judgment of competence by others, specifically measures of peer acceptance (Nixon, 2001). Studies show that children with ADHD receive low ratings in peer-nomination and peer-ratings measures.…”
Section: Adhd and Social Skillsmentioning
confidence: 99%
See 3 more Smart Citations